Differential heat of ammonia adsorption and adsorption mechanism in Са4Na4A zeolite - Oybek, Ergashev; Bakhronov, Khayot; Sobirjonova, Surayyo; Koxkharov, Mirzokhid; Mamadaliyev, Utkurbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents the experimentally obtained values of differential enthalpy of ammonia adsorption at 303 K in Ca4Na4A (Horst-50/50) zeolite of the LTA type. The enthalpy values were measured using a modified Tian-Calvet-type DAC-1-1A microcalorimeter connected to a universal high-vacuum device. The regular relationship between the amount of ammonia adsorption and differential enthalpy in Ca4Na4A (Horst-50/50) zeolite, as well as the adsorption mechanism from the initial region to the condensation heat of ammonia, and the filling of the zeolite volume by ammonia molecules, was determined. Under experimental conditions, the adsorption capacity of Ca4Na4A (Horst-50/50) zeolite for ammonia was found to be 8.8 mmol/g. The differential heat values were found to vary according to the number of Na+ and Ca2+ cations in the zeolite structure, with ammonia molecules forming pentameric 5NH3:Na+ ion-molecular complexes with sodium cations and dimeric 3NH3:Ca2+ ion-molecular complexes with calcium cations in the first coordination sphere of the zeolite.